Catechol-modified chitosan hydrogel containing PLGA microspheres loaded with triclosan and chlorhexidine: a sustained-release antibacterial system for urinary catheters. (28th May 2022) - Lin, Chengxiong; Huang, Zhengyu; Wu, Tingting; Xu, Weikang; Zhao, Ruifang; Zhou, Xinting; Xu, Zhibiao
Abstract: Blockage and infection are common in hospitals, especially with long-term indwelling catheters, due to bacterial adhesion, colonization, and other reasons. A drug-sustained-release antibacterial coating for urinary catheters was described in this paper. Chlorhexidine (CHX) and triclosan (TCS) were encapsulated in poly(lactic-co-glycolic acid) microspheres and mixed with a modified chitosan hydrogel deposited on the surface of silicone rubber. The results showed that drugs can be released continuously more than 35 days. Catechol-modified chitosan (Chi-C) hydrogel was successful synthesized according to FT-IR and UV spectrophotometry, as well as 1 H NMR. Furthermore, the coating with CHX and TCS presented stable antibacterial ability compared to the other groups. The results of CCK-8 revealed that the coating was cytotoxic-free and had a wide range of applications. The findings could provide a new drug sustained-release system and hydrogel-microsphere assembly for urinary catheters. Highlights: The microspheres presented a sustained release more than 40 days with a remarkable initial burst release. The microspheres/catechol-modified chitosan (Chi-C)/silicon rubber system emerged stable binding ability in liquid environment more than 14 days. The Chi-C/chlorhexidine (CHX)+triclosan (TCS) microspheres system presented better antimicrobial property for entire experiment period. The coated samples showed no significant difference for relative growth rate (RGR) compared to different groups. Graphical Abstract: UF0001